Measuring respiratory and heart rate using a fiber optic interferometer: A pilot study in a neonate model - Cubík, Jakub; Kepak, Stanislav; Wiedermannova, Hana; Vrtkova, Adela; Burckova, Hana; Zarubova, Pavla; Fernandez, Carlos; Pavlicek, Jan; Jargus, Jan; Vasinek, Vladimir (Frontiers in Pediatrics, 2022)
Introduction: The study aim was to test the safety and efficacy of a pad with optic fibers developed for monitoring newborn respiratory rate (RR) and heart rate (HR). Methods: Thirty New Zealand White rabbits were included, divided by weight into three groups. RR and HR were measured using two methods for each rabbit: ECG electrodes as the reference method and a newly developed pad with an experimental fiber optic system (EFOS) as the experimental method. Results: Analysis was performed on data for 29 rabbits (10 female, 34%; 19 male, 66%). EFOS performed better at measuring RR compared with HR. RR values did not differ significantly between the methods for the whole group (p = 0.151) or within each sex (female: p > 0.999; male: p = 0.075). Values for HR, however, did differ between methods for the whole group of animals (p < 0.001) and also within groups by sex (female: p < 0.001; male: p = 0.006). Conclusion: The results of this preclinical study demonstrate the potential of this non-invasive method using a fiber optic pad to measure HR and RR.